Accessibility and Urban Mobility In Triângulo Mineiro - Minéu, Humberto Ferreira Silva; Silveira, Leonardo José; Pacheco, Rafael Araújo; Ferreira, William Rodrigues (Geografares, 2014)
This article discusses the accessibility and urban mobility at public spaces – squares – of three towns in Triangulo Mineiro, Minas Gerais, Brazil. The objective is to analyze the accessibility and urban mobility, according with specifics laws and current norms. The results showed some inadequacies concerning the conditions of accessibility and deficiencies in urban mobility. The analysis presents the necessity to adequate the infrastructures of the public spaces and an effective urban politic, which promotes the social inclusion, with accessibility and mobility to all citizens.